Chestvovaniia pamiati Tarasa Shevchenko . Chestvovaniia pamiati Tarasa Shevchenko . Honoring the Memory of Taras Shevchenko . Чествования памяти Тараса Шевченко - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. A political rally in which Ukrainian deputies also take part, to honor the memory of Taras Shevchenko. Featured in the program: Chernovil, Viacheslav (Head of the Political Party "Narodnyi Rukh Ukrainy" [People's Movement of Ukraine]) Политический митинг с участием украинских депутатов, посвящен чествованию памяти Тараса Шевченко. В программе участвуют: Черновол, Вячеслав (Глава политической партии "Народный рух Украины")